2022
DOI: 10.1038/s41396-022-01342-4
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacteroidetes use a conserved enzymatic cascade to digest diatom β-mannan

Abstract: The polysaccharide β-mannan, which is common in terrestrial plants but unknown in microalgae, was recently detected during diatom blooms. We identified a β-mannan polysaccharide utilization locus (PUL) in the genome of the marine flavobacterium Muricauda sp. MAR_2010_75. Proteomics showed β-mannan induced translation of 22 proteins encoded within the PUL. Biochemical and structural analyses deduced the enzymatic cascade for β-mannan utilization. A conserved GH26 β-mannanase with endo-activity depolymerized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Most of these genes were affiliated to Flavobacteriaceae. Whilst the importance of Bacteroidetes- mediated polysaccharide cycling has been well documented in surface waters [ 21 , 23 , 38 , 39 ], we observed that the relative abundance of Bacteroidetes CAZyme genes generally increased with depth, except for a large decrease in near-bottom waters (Fig. 2 A).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Most of these genes were affiliated to Flavobacteriaceae. Whilst the importance of Bacteroidetes- mediated polysaccharide cycling has been well documented in surface waters [ 21 , 23 , 38 , 39 ], we observed that the relative abundance of Bacteroidetes CAZyme genes generally increased with depth, except for a large decrease in near-bottom waters (Fig. 2 A).…”
Section: Resultsmentioning
confidence: 55%
“…Recently, these polysaccharides were detected in surface waters during a diatom bloom [ 47 ] and associated Bacteroidetes spp. were shown to possess PULs for their degradation [ 21 , 23 , 39 ]. Since algal cell walls evolved to be highly resistant to a wide range of biotic stresses like enzymatic hydrolysis, their pectic and hemicellulosic glycan components may persist longer than internal storage glycans like laminarin [ 47 ] and, thus, be more likely to sink to deeper waters.…”
Section: Resultsmentioning
confidence: 99%
“…This utilization of dissolved algal glycans represents an essential part of the marine microbial loop 6 and thus the global carbon cycle. Particularly prominent in this process are marine members of the phylum Bacteroidota 7 9 . These bacteria target algal polysaccharides by specific sets of enzymes and transporters encoded in genomic islands, termed polysaccharide utilization loci (sg.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the phylum Bacteroidetes are selected in such glycan‐rich environments (McKee et al, 2021). Recent studies showed the utilization of a diverse range of algal glycans by members of this phylum (e.g., Barbeyron et al, 2016; Beidler et al, 2023; Ficko‐Blean et al, 2017; Hehemann et al, 2012; Reisky et al, 2019; Robb et al, 2022; Unfried et al, 2018). Their carbohydrate‐active enzymes, or CAZymes, are often co‐located with transporters and regulatory proteins in polysaccharide utilization loci (PULs) within bacterial genomes (Martens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%